Heat transfer in Ar and N2 doped solid CO - Romanova, T.; Stachowiak, P.; Jezowski, A.; Trzebiatowski, W. (Recent Contributions to Physics, 2015)
Investigations of thermal conductivity of dielectric crystals play a special role in solid state physics. The obtained information can be interesting both for theory and experiment. Introducing an impurity in the crystal enables to study influence of the thermal excitations modified by the impurity on the thermal conductivity or scattering of the heat carrier by the impurities.In CO-Ar solution the isotopic effect occurs, i.e. effect caused by the difference of the masses of the impurities and the host atoms. This leads to additional mechanism of phonon scattering.
Keywords: thermal conductivity, defects, phonon scattering, impurity